Do financial crises increase income inequality?. (November 2021) - Bodea, Cristina; Houle, Christian; Kim, Hyunwoo
Highlights: We find strong evidence that currency, banking, inflation and debt crises increase economic inequality. The empirical analysis addresses issues related to reverse causality, which have plagued previous empirical tests. We account for the slow-moving nature of the dependent variable as well as for measurement error in the dependent and independent variables. We find that the effect of financial crises on economic inequality is particularly strong in the long run. Abstract: This paper investigates the impact of economic crises on income inequality. Important evidence has emerged that in the aftermath of crises politics becomes polarized and economists have linked this to greater differences in income due to crises. However, the evidence on whether crises are linked to divergent incomes is weak and plagued by i) the possibility of a reverse effect going from great disparity in incomes to major economic crises; ii) the persistent nature of income inequality; and iii) important measurement error in both the dependent and independent variables. We use the longest time stretch of available data on crises and types of crises (Reinhart and Rogoff, 2011) and income inequality (Solt, 2009), as well as decade averaged data, general method of moments and error-correction models to more credibly estimate the complex relationship between crises and inequality. We find strong evidence that currency, banking, inflation and debt crises increase inequality, particularly in the long run.